EKSPLORASI MANIFESTASI MORALITAS PESERTA DIDIK DALAM PEMBELAJARAN SENI TARI DAN SENI SUARA BERBASIS PROYEK KOLABORATIF: Studi Deskriptif Kualitatif di SMA Kristen Anak Panah Nabire - Widjaja, Hana Sumiati; Hartono; Rokhman, Fathur; Wagiran (STKIP Subang, 2026)
This qualitative descriptive study explores the manifestations of student morality in collaborative project-based learning in dance and vocal arts education at SMA Kristen Anak Panah Nabire, Indonesia. This research aims to investigate how aesthetic experiences and collaborative artistic activities contribute to the internalization and expression of moral values. Data collection was conducted through participant observation, in-depth interviews, and documentation analysis during the